DsrA confers resistance to oxidative stress in Salmonella enterica serovar Typhimurium. (March 2021) - Dong, Rui; Qin, Xiaojie; He, Shoukui; Zhou, Xiujuan; Cui, Yan; Shi, Chunlei; He, Yiping; Shi, Xianming
Abstract: Non-coding small RNAs (sRNAs) have been recognized as major regulators of bacterial stress response. The sRNA DsrA is known to be involved in acid tolerance response of Salmonella, while its role in the response to other stress factors such as oxidants remains unclear. The aim of this study was to characterize the function of DsrA in oxidative stress resistance of S. Typhimurium. Therefore, comparison analysis of survival rates, enzyme activity and gene expression patterns among the wild-type (WT), dsrA -deletion mutant (Δ dsrA ) and complemented strain (Δ dsrA- C) was carried out in this study. It was found that deletion of DsrA led to a 2.5-log population reduction after exposure of S. Typhimurium to 3 mM H2 O2 for 1 h in addition to cell membrane damage and intracellular ATP depletion. Moreover, the expression level of catalase and superoxide dismutase encoding genes ( katEGN, sodABC ) in the Δ dsrA mutant was significantly ( P  < 0.05) lower than that in WT or Δ dsrA- C, and the activity of these two enzymes was also decreased in the Δ dsrA mutant. Meanwhile, the NAD + /NADH ratio surged in Δ dsrA compared to the wild-type, which indicated the redox homeostasis was altered in the absence of DsrA. These results suggested that DsrA stimulates oxidative stress resistance in S. Typhimurium possibly by regulating the expression of antioxidant enzymes as well as maintaining the intracellular redox balance. Highlights: DsrA was required for S. Typhimurium survival under oxidative stress. DsrA deletion led to membrane damage and ATP depletion in S. Typhimurium. DsrA deletion broke the redox balance in S. Typhimurium. DsrA deletion reduced the expression level of antioxidase-related genes.